A 40-43-Gb 16 demultiplexer in SiGe technology. - Ong, A.
A fully integrated OC-768 clock and data recovery IC with SFI-5 1:16 demultiplexer is designed in a 120-GHz/100-GHz (fT/fMAX) SiGe technology. The 16 2.5-Gb/s outputs and additional deskew channel are compliant with the Serdes Framer Implementation Agreement Level 5 specification. The measured bit-error rate is <10-15. The measured jitter tolerance exceeds the mask specified in G.8251. The IC operates with 1.8-V and -5.2-V supplies and dissipates 7.5 W.
Keywords: 1.8 V; 100 GHz; 120 GHz; 2.5-Gb/s outputs; 40 to 43 Gbit/s.; 5.2 V; 7.5 W; BICMOS CDR IC; G.8251.; OC-768 IC; SONET; Serdes Framer Implementation Agreement Level 5 specification; SiGe technology; Bang-bang.; Bit-error rate; Charge pump; Clock and data recovery IC; Deskew channel; Integrated SFI-5 1:16 demultiplexer; Jitter tolerance; Optical fiber communication; Phase detector; Voltage-controlled oscillator